Endocrine disruptors and the tumor microenvironment: A new paradigm in breast cancer biology. (5th December 2017) - Burks, Hope; Pashos, Nicholas; Martin, Elizabeth; Mclachlan, John; Bunnell, Bruce; Burow, Matthew
Abstract: Breast cancer is one of the most frequently diagnosed malignancies in women and is characterized by predominantly estrogen dependent growth. Endocrine disruptors (EDCs) have estrogenic properties which have been shown to increase breast cancer risk. While the direct effects of EDCs on breast cancer cell biology and tumor progression have been well studied, the roles for EDCs on tumor microenvironment composition, signaling and structure are incompletely defined. Estrogen targeting of tumor stromal cells can drive paracrine signaling to breast cancer cells regulating tumorigenesis and progression. Additionally, estrogen and estrogen receptor signaling has been shown to alter breast architecture and extracellular matrix component synthesis. Unsurprisingly, EDCs have been shown to induce structural changes in the mammary gland as well as increased collagen fibers in the tissue stroma. Previous work demonstrates that human mesenchymal stem cells (hMSC) are essential components of the tumor microenvironment and are direct targets of both estrogens and EDCs. Furthermore, estrogen–stem cell cross talk has been implicated in breast cancer progression and results in increased tumor cell proliferation, angiogenesis and invasion. This review aims to dissect the possible relationship and mechanisms between EDCs, the tumor microenvironment, and breast cancer progression. Highlights: EDCs affect breast cancer incidence and progression through estrogen signaling. EDC exposure alters breast development and adipogenesis, promoting tumor formation. EDC exposure exerts an oncogenic effect on the extracellular matrix. EDCs promote breast cancer progression through altered signaling in the tumor stroma.